Formation and development of innovative infrastructure in the higher education system - Khamraeva Sayyora Nasimovna; Mardonova Guzal Mamatkul kizi (THE INNOVATION ECONOMY, 2026)
Currently one of the key drivers of economic growth is innovation and knowledge, which are receiving increasing attention. In this regard, the higher education system is not limited to training qualified specialists but also actively participates in the creation and development of new knowledge. The innovative infrastructure of higher education encompasses a set of institutions, resources, and mechanisms that ensure collaboration between science, education, and industry. The main purpose of this article is to explore the scientific and theoretical foundations of developing innovative infrastructure in higher education and to scientifically substantiate the objective necessity of its advancement